Karakteristik Spasial dan Temporal Kebakaran Lahan Gambutdi KHG Pulau Rangsang - Nur Hidayati; Sigit Sutikno; Nurul Qomar (JURNAL TEKNIK, 2022)
Peatland fires are a serious problem in the Peat Hydrological Unit (PHU) of Rangsang Island for the last 20 years. The level of peatland fires that are quite severe can only be extinguished by rainfall. The analysis of spatial and temporal characteristics of peatland fires related to distribution of hotspots with a confidence level >60%, using Landsat imagery and pattern formed as an indication of the burned area caused by the hotspot data in the last 20 years (2001-2020). This analysis is expected to provide a reference that is able to explain the characteristics of peatland fires, including total area burned, duration of peat fire and the rate of peat fire that occurs every year. The results of hotspot analysis are overlapped with on-off layer technique of Landsat imagery that has been composited band using GIS (Geographic Information System). delineation results are used as the basis for obtaining the characteristics of peatland fires in the Rangsang Island KHG.The results of the delineation were used as the basis for obtaining the characteristics of peatland fires in the Rangsang Island KHG. In this study, the total area of fires that occurred in Rangsang Island KHG in a period of 20 years reached 114,982.71 ha, with a total duration of 308 days of fire.